K R Narayanan: crusader of social justice - Chandra, Ramesh; Mittra, Sangh (New Delhi Commonwealth, 2019)
The theme covers the life sketch including speeches and writings of Shri K.R. Narayanan, the eleventh Rashtrapati of India.
Keywords: President